Implicações do câncer infantil na dinâmica familiar - Salvagni, Adelise (2014)
The present study has as objective to know the implications of childhood cancer on family dynamics. To this end, it was conducted with a clinical study-qualitative comprising three case studies with families of children who had received the diagnosis of childhood cancer and carried out treatment in a city in southern Brazil. The data collection were through semi-guided interviews with parents and teenage brothers; with children, both the patient and their younger brothers, applied the technique of drawing the family with story; In addition, observations were performed at the hospital and the homes of the families. The data were submitted to content analysis. The results are presented in three articles, so that each one of them deals with a case and emphasizes one of the family relations. One of them treats on the marital relationship, the other about parental and, finally, one about the fraternal relationship. The article that reflects about the conjugal subsystem demonstrates that the conjugal relationship is affected by the experience of the child illness, which it demands by the couples adjustments and reorganization of roles. There is a union between the spouses; however, it occurs in the direction to the child care, while the intimate aspects of the relationship are in the background at the beginning of the treatment. The second article, which addresses parenting facing the situation of illness, suggests that the focus of the family are intended for child care at this point. As a result, there is an approximation between parents and the fallen ill daughter and a withdrawal from the other daughters. The third and final article, which discusses the fraternal relationship in the context of the disease, points to a relationship of unity and care between the brothers to deal with the situation and take account of the absence of the mother in the home environment. Considering the results presented, it can be said that, generally speaking, families joined together to confront the event. In view of this context, it can be conclude on the importance of studies and actions in health that may consider the family on systemic vision, in order to understand the interrelation between family subsystems in these terms and foment health promotion programs that may consider all the families and not just those who engage directly with the child care at the hospital.